ANALISIS FRAMING BERITA PEMILIHAN KEPALA DAERAH POLEWALI MANDAR PERIODE 2014-2019 DI HARIAN RADAR SULAWESI BARAT - Muhammad Massyat (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2016)
This study discusses the framing of Polewali Mandar regional head election news for the 2014-2019 period published in Radar Sulbar Daily. How is a news constructed to influence the opinion of the reader. The method used in obtaining data is the process of elaborating text or documentation. The results of the study show that the Radar West Sulawesi Daily in the issue of Polewali Mandar regional election carries a certain discourse as part of one candidate.